2020
DOI: 10.3390/su12187435
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Fast Food Restaurant Attributes on Customer Satisfaction, Revisit Intention, and Recommendation Using DINESERV Scale

Abstract: The fast food restaurant business is one of the fastest-growing industries in the world. International and local restaurant chains are trying to satisfy the demands of customers for a variety of products and services. Along with changing market trends, customers are now becoming more sophisticated and demanding. Customer satisfaction is an essential business issue, as entrepreneurs have realized that favorable customer feedback is key for a long-term sustainable operation. Customers who have an excellent exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
2
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(79 citation statements)
references
References 36 publications
6
63
2
8
Order By: Relevance
“…ey found that "food quality" is the most important criterion as the customers' are concerned about their health issues such as obesity and diabetes. e current research findings are also not consistent with the findings of the research conducted by Chun and Nyam-Ochir [32]. ey found that food quality and three other criteria of a restaurant positively influence customers' satisfaction.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…ey found that "food quality" is the most important criterion as the customers' are concerned about their health issues such as obesity and diabetes. e current research findings are also not consistent with the findings of the research conducted by Chun and Nyam-Ochir [32]. ey found that food quality and three other criteria of a restaurant positively influence customers' satisfaction.…”
Section: Discussioncontrasting
confidence: 98%
“…It is difficult to explain this result, but it might be related to customers' preference in which customers' preference toward a restaurant is very much influenced by customers' satisfaction. A study indicated that customers' satisfaction has a positive influence on Advances in Fuzzy Systems customer revisit intention and likelihood of recommendation [32]. e preferred restaurant also probably has positive criteria such as food quality, service quality, and customers' satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Kepuasan konsumen dapat digambarkan sebagai sejauh mana produk atau layanan yang dipilih dapat memenuhi atau melebihi harapan konsumen (Chun & Nyam-Ochir, 2020). Indikator yang digunakan berdasarkan Zeithaml et al (2009) yaitu : Fulfillment, Pleasure dan Ambivalence.…”
Section: Kepuasan Konsumen (M)unclassified
“…Debido a esto han tenido un constante crecimiento, por lo cual las cadenas de restaurantes internacionales y locales están intentando satisfacer la demanda de los clientes con una variedad de productos y servicios innovadores, debido a que la población cada vez opta por utilizar los restaurantes de comida rápida de acuerdo con su estilo de vida, causando grandes cambios en las nuevas tendencias de consumo (Chun & Nyam-Ochir, 2020).…”
Section: La Industria De Comida Rápida Y El Servicio De Deliveryunclassified